2013
DOI: 10.1063/1.4804582
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the energy of terahertz radiation from plasma produced by intense femtosecond laser pulses

Abstract: Terahertz (THz) radiation from atomic clusters illuminated by intense femtosecond laser pulses is investigated. By studying the angular distribution, polarization properties and energy dependence of THz waves, we aim to obtain a proper understanding of the mechanism of THz generation. The properties of THz waves measured in this study differ from those predicted by previously proposed mechanisms. To interpret these properties qualitatively, we propose that the radiation is generated by time-varying quadrupoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Jahangiri et al [9], [10] also stated that THz pulse energy dependence on laser energy demonstrates nonlinear growth according to "square law" without any saturation, at least, up to 70 mJ per laser pulse (that was a maximum available value of femtosecond pulse energy in the experiments, which corresponds to the vacuum intensity ∼ 10 17 W/cm 2 ). Jahangiri et al [10] suggested that this low-frequency radiation originates from time-varying electrical quadrupoles produced by charge separation due to ponderomotive force.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…Jahangiri et al [9], [10] also stated that THz pulse energy dependence on laser energy demonstrates nonlinear growth according to "square law" without any saturation, at least, up to 70 mJ per laser pulse (that was a maximum available value of femtosecond pulse energy in the experiments, which corresponds to the vacuum intensity ∼ 10 17 W/cm 2 ). Jahangiri et al [10] suggested that this low-frequency radiation originates from time-varying electrical quadrupoles produced by charge separation due to ponderomotive force.…”
mentioning
confidence: 97%
“…There are a number of experiments confirming high efficiency of THz generation. Recently, the intense THz generation in an argon cluster beam excited by femtosecond laser pulses was reported in [8]- [10]. Nagashima et al [8], [9] observed more than two orders of magnitude enhancement in total THz pulse energy from argon cluster beam compared to that from gaseous argon, at equal average atomic density.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of laser-cluster interaction, e.g., the deuterium-deuterium nuclear fusion, 1-3 plasma waveguide generation, 4 x-ray, 5 terahertz radiation, 6 the cluster size in a gas jet is an important parameter for the understanding of these experimental results. Usually, a clustered gas jet is produced by the adiabatic expansion of gas under a high backing pressure through a conical nozzle into vacuum and the average cluster size is estimated by Hagena scaling laws.…”
Section: Introductionmentioning
confidence: 99%